Pathophysiology, clinical manifestations and current management of IL-1 mediated monogenic systemic autoinflammatory diseases, a literature review - Yandie Li; Meiping Yu; Meiping Lu (Pediatric Rheumatology Online Journal, 2022)
Abstract Background Systemic autoinflammatory diseases (SAIDs) are hyperinflammatory and immune-dysregulation conditions that present in childhood. This kind of disease is a rare disease with early-onset, severe condition and difficult diagnosis, which seriously affects the growth and development of children. Most children need a genetic diagnosis. However, with the limitation of access to genetic testing and the detection of somatic mutations, the diagnosis of SAIDs remains challenging. IL-1 is one of the important cytokines involved in the pathogenesis of SAIDs. Here we briefly review monogenic SAIDs mediated by aberrant IL-1 production, with the aim to further understand the pathogenesis, clinical manifestations and treatments of IL-1 mediated SAIDs. Methods Literature reviews were performed using “PubMed” and “Web of Science” by searching for the terms “autoinflammatory diseases” and “IL-1”. Results Monogenic SAIDs mediated by IL-1 include MKD, FMF, TRAPS, PAAND, PAPA, CAPS, DIRA, Majeed syndrome, NAIAD, NLRC4-MAS, PFIT, APLAID. Monogenic SAIDs have early onset, various clinical manifestations and difficult diagnosis, so early recognition and early treatment can reduce the complications and enhance the quality of life. Conclusions There are many kinds of IL-1 mediated SAIDs. Pediatricians should be alert to SAIDs in the face of the patients with repeated fever, repeated rash and poor effect of routine treatment. The patients should be carried out with gene testing and treatment in time.